“A man is a man and a woman is a woman; everything else is hanky-panky”: social representations of transsexuality on internet comments - Vitali, Marieli Mezari; Castro, Amanda; Caravaca-Morera, Jaime; Soratto, Jacks (Saúde e Sociedade, 2019)
The objective of this study was to identify social representations about transsexuality based on the comments described in social networks (Facebook and Instagram). This is a qualitative study with a descriptive exploratory approach, using the method of documentary research and based on the theory of social representations. Data were collected from some series of reports of a Brazilian journalistic program with national impact. Data analysis was performed based on content analysis with the aid of Atlas.ti software. The results allowed the generation of 14 codes, which were grouped into four categories: origin of transsexuality, attitude towards transsexuality, definition of transsexuality and trans vulnerability. It was possible to identify the lack of information of the internauts, especially the lack of respect for the transsexual people, justified by a blaming, oppressive, fundamentalist speech that cooperates for their vulnerability, allocating them at the margins of the society of right. These results conclude that it is necessary to expand effective public policies for the transgender population and thus guarantee the human rights and citizenship for these people.